Asociación entre obesidad y el score DAS28 –VSG en pacientes mujeres con Artritis Reumatoide del Hospital Regional Docente de Trujillo - Fernández Valencia, Cristina Beatriz (2021)
Rheumatoid Arthritis is a chronic inflammatory joint disease of autoimmune nature, affects 1% of the world population and is related to loss of physical function, quality of life and high prevalence of other comorbid diseases. The American College of Rheumatology recommends the use of the 28 joint count disease activity index with sedimentation rate measurement or C-reactive protein (DAS28 - ESR) as a routine evaluation as it is an accurate reflection of the activity of the disease. Obesity is a prevalent comorbidity in patients with rheumatoid arthritis, it is estimated that between 11 - 31% of patients with arthritis are obese. The impact of obesity in these patients is uncertain, it is considered that a higher body mass index is a potential predictor of a more active, severe, refractory disease with a poor response to treatment, depending on the inflammatory nature of the two conditions.